Ethyl Acetate Fraction of Moringa oleifera Leaves Induces Cell Cycle Arrest on T47D Breast Cancer Cell via G0/G1 through Cyclin D1 Expression - Riza Apriani; Tati Herlina; Shabarni Gaffar (Jurnal Kimia Valensi, 2020)
Cancer is a disease that is the leading cause of death worlwide. Exploration of a natural product containing anticancer agent provides a promising line for research on cancer. One of plant that used in traditional medicine for the cancer treatment is Moringa oleifera. The previous study has reported that the n-hexane fraction of M. oleifera leaves induce apoptosis and cell cycle arrest in T47D cells. Based on the preliminary result, ethyl acetate fraction of M. oleifera (EMO) leaves showed medium cytotoxic activity on T47D cells with IC50 values of 243.58 μg/mL and induced apoptosis cell death. This study was carried out to investigate the anticancer activity mechanism on the cellular and molecular basis of EMO against T47D breast cancer cell line by observing cell cycle progression and Cyclin D1 expression level. Analysis of the cell cycle was performed using flow cytometry and cyclin D1 expression was analyzed using the immunocytochemistry method. The result shows that EMO induced cell cycle arrest in G0/G1 phases. Immunocytochemistry assay showed that the EMO decreased expression of  cyclin D1. This result indicates that EMO has a potential compound to be explored as chemo preventive agent for breast cancer.